2016
DOI: 10.1016/j.chemosphere.2015.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Maternal transfer of dechloranes and their distribution among tissues in contaminated ducks

Abstract: h i g h l i g h t sRelatively serious contamination of DP was found in the e-waste recycling sites, Taizhou. Lipid pool, liver sequestration and blood-barrier affect tissue distribution of DP and its analogues. The maternal transfer extent of Dec 602 was over one. The stereo-selective accumulation of DP occurs among duck tissues. The monodechlorinated products in duck likely originated from the exterior environment. a r t i c l e i n f o t r a c tThe tissue concentrations of dechlorane plus and its analogues … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Number of articles about e-waste recycle between year's 2010 and 2020. These data were obtained from Brazilian Government Data Bank for scientific publications, between year's 2010 to 2020 (Capes, 2000) The articles about contamination really represents the presence of e-waste chemical pollutants in the water (Wu et al, 2015), soil (Quan et al, 2015), plants (Wang et al, 2012), animals (Wu et al, 2016), and humans (Asante et al, 2012) near recycling areas (Figure 5). The articles about recycling (Figure 6) represents not only formal recycle, but mainly unconventional and dangerous recycle methods for environment.…”
Section: E-waste Contaminationmentioning
confidence: 99%
“…Number of articles about e-waste recycle between year's 2010 and 2020. These data were obtained from Brazilian Government Data Bank for scientific publications, between year's 2010 to 2020 (Capes, 2000) The articles about contamination really represents the presence of e-waste chemical pollutants in the water (Wu et al, 2015), soil (Quan et al, 2015), plants (Wang et al, 2012), animals (Wu et al, 2016), and humans (Asante et al, 2012) near recycling areas (Figure 5). The articles about recycling (Figure 6) represents not only formal recycle, but mainly unconventional and dangerous recycle methods for environment.…”
Section: E-waste Contaminationmentioning
confidence: 99%
“…DP exhibits some POP-like properties, one of which is its ability to accumulate in animals and humans [ 2 , 4 , 5 ]. Studies on animals [ 6 , 7 ] (e.g., fish and poultry) have given evidence on DP transfer from parents to offspring, and Ben’s study [ 8 ] further confirmed the transplacental transfer of DP in humans. Although its health risk to humans has not yet been better understood until now, animal experiments have shown that exposure to DP in early life could impact axonal growth, musculature, and motor behavior in embryo–larval zebrafish [ 9 ], and regulate mRNA expression in chicken embryos [ 10 ].…”
Section: Introductionmentioning
confidence: 96%
“…Due to the significant linkage between prenatal exposure and adverse health outcomes at birth and/or in later life, exposure of pregnant women to persistent organic contaminants is an ongoing public health concern [ 11 ]. The transplacental transfer and potential toxicity to animals [ 6 , 7 ], together with POP-like properties [ 2 , 4 , 5 ], implies that we ought to pay specific concern to in utero exposure to DP in humans.…”
Section: Introductionmentioning
confidence: 99%
“…Dechlorane Plus (DP) is a polychlorinated flame retardant designed to replace Brominated flame retardants or Mirex (Ji et al, 2018 ), and it is widely used in plastic roofing materials, electrical wires, hard disk connectors of computers, and other polymeric systems (Ren et al 2008). DP is found common in the aquatic environment Sun et al 2017;Tao et al 2015;Wu et al 2016), with a half-life of about 24 years in the water environment. It is a typical persistent organic pollutant and has an effect of bio-enrichment and bio-fortification in the biota (OxyChem 2007;Yu et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Hoh et al first discovered the existence of DP in the environment in 2006. Some studies show that DP accumulates in female herring gulls, crucian carp, ducks, lake trout, and mud carps, and that it is maternally transferred to their eggs (Guo et al 2017;Gauthier and Letcher 2009;Wu et al 2016).…”
Section: Introductionmentioning
confidence: 99%